Development and Psychometric Properties of a Scale for Assessing Parents’ Attitudes towards AAC for Children with Complex Communication Needs - Zlatić, Aleksandar; Arsenić, Ivana; Mentus Kandić, Tatjana; Veljković, Zorica (Psihološka istraživanja, 2026)
Augmentative and Alternative Communication (AAC) encompasses a wide range of strategies and technologies designed to support individuals with complex communication needs. Although the effectiveness of AAC interventions has been well documented, parental attitudes and knowledge remain crucial factors in the successful implementation of these methods. The aim of this study is to develop and conduct an initial psychometric evaluation of the instrument designed to assess parental attitudes towards AAC in the local context. The study included 50 parents of children with complex communication needs. Data were analysed using Partial Least Squares Path Modelling (PLS-PM). The initial measurement model demonstrated satisfactory unidimensionality and internal consistency for the majority of constructs (DG rho> 0.70). Several items exhibited low factor loadings, while the construct “General Attitudes” showed marginally lower reliability. After removing problematic items, improvements were observed in reliability and convergent validity (increased DG rho and AVE), supporting the adequacy of the purification process. However, the HTMT analysis indicated limited discriminant validity, particularly for the constructs with a reduced number of remaining indicators, which is consistent with the known characteristics of the PLS-PM estimation in small samples. The structural model confirmed the importance of parental knowledge of AAC as a key predictor of readiness to implement the AAC strategies. The developed instrument represents a functional preliminary version of the scale for assessing parental attitudes towards AAC. Further validation on larger and more diverse samples, as well as the development of additional items aimed at strengthening construct validity, is recommended.